Cytoplasmic genetic diversity of potato varieties bred in Russia and FSU countries - Т. A. Gavrilenko; N. S. Klimenko; N. V. Alpatieva; L. I. Kostina; V. A. Lebedeva; Z. Z. Evdokimova; O. V. Apalikova; L. Y. Novikova; O. Yu. Antonova (Вавиловский журнал генетики и селекции)
Male sterility in potato is little studied since traditional breeding is based  on the vegetative reproduction of highly heterozygous tetraploid varieties. The rapid development of hybrid diploid breeding contributes to growing interest in studying the male sterility of this important crop. In this work, a set of 6 cytoplasmic markers was employed to describe cytoplasmic genetic diversity of 185 potato cultivars bred in Russia and FSU countries. Three cytoplasm types were identified, T (40.0 %), D (50.8 %) and W/γ (8.7 %), which according to literature  are associated with male sterility. With a single exception (0.5 %), cytoplasm types characteristic of male fertile forms (A, P) were not found in the subset  of 185 cultivars. A comparison of these results with previously published data suggested expanding the subset  to up to 277 cultivars, all developed in Russia or FSU countries;  however,  the resulting  differentiation into three cytoplasm  types (T, D and W/γ) was nearly the same. Fertility phenotyping helped identify both  male-sterile and male-fertile genotypes within the three groups  of varieties with T-, D- and W/γ-type cytoplasm. Fifteen genotypes differing in cytoplasm  type and male sterility/fertility traits were selected for direct sequencing of 8 mtDNA loci. Fragments of the  nad2, nad7, cox2, atp6 and  CcmFc genes  were identical  in all 15 selected genotypes. The polymorphism, detected in the rps3, atp9 and CcmFc loci, was not associated with male sterility. Two SNPs in the nad1/atp6 and nad2 loci differentiated 7 genotypes with W/γ-type cytoplasm into five genotypes with tetrad sterility, and two with fertile pollen. The results of an NGS analysis confirmed  the association of these  SNPs with tetrad sterility in a larger set of 28 genotypes of different origin, all with W/γ-type cytoplasm.  A heteroplasmy state  was observed both in male-sterile and in male-fertile genotypes.